Birth oxidative stress and the development of an antioxidant system in newborn piglets. (December 2013) - Yin, J.; Ren, W.; Liu, G.; Duan, J.; Yang, G.; Wu, L.; Li, T.; Yin, Y.
Abstract: Birth oxidative stress is an oxidative response to a sudden transition process from maternal mediated respiration in uterus to autonomous pulmonary respiration outside the uterus. Meanwhile, oxidative stress has been demonstrated to be associated with various pathologies recorded in newborns. So, this research aimed to study the oxidative stress and the development of antioxidant system in newborn piglets. The measured variables include plasma lipid, protein and DNA oxidant injury, the activities of plasma antioxidant enzymes and the jejunal and ileal antioxidant gene expressions at 1, 7, 14, and 21 days after birth. Meanwhile, the nuclear factor erythroid 2-related factor 2 (Nrf2), transcription factor p65, and tumor protein 53 (p53) were determined by western blot. The results showed that newborn piglets suffered seriously from birth oxidative stress because of the naive antioxidant system. In addition, oxidant injury activated Nrf2 signaling pathway, resulting in the expression of antioxidant genes and release of antioxidant enzymes. With the development of antioxidant system, the oxidative balance gradually recovered on Day 7 after birth. In conclusion, birth caused oxidative stress and the oxidative balance gradually recovered with the development of antioxidant system.